The correlation between Candida colonization index and risk factors of invasive candidiasis among patient in intensive care unit - Tiyakusuma, Evira; Noorhamdani AS; Ruliatna, Etty Fitria (Indonesian Society for Clinical Microbiology (Perhimpunan Dokter Spesialis Mikrobiologi Klinik Indonesia), 2024)
Background: Invasive candidiasis is frequently found among patients hospitalized in intensive care units (ICU) due to immunocompromised state and performed the invasive procedure. To simplify invasive candidiasis screening, the Candida colonization index (CCI) was performed on the patients. But the implication of the CCI towards the risk factors of invasive candidiasis has never been evaluated before. Hence this study aims to evaluate the correlation between the CCI and invasive candidiasis risk factors and antifungal therapy. Methods: During this study, CCI was collected from routine clinical culture results of the ICU patients while information regarding risk factors was obtained from routine follow-ups conducted on patients in the ICU. This study showed a significant correlation between the CCI, and several risk factors of invasive candidiasis, such as sequential organ failure assessment (SOFA) score, number of invasive medical instruments, and Candida score. Results: These results support the hypothesis that proposes a certain correlation between CCI and risk factors of invasive candidiasis. There is also a significant correlation between antifungal therapy and the prevalence of Candida non-albicans colonization. Conclusion: This study also supports the hypothesis that proposes shifting in the distribution of Candida species causing invasive candidiasis from Candida albicans to Candida non-albicans due to misappropriate use of antifungal therapy.